2014
DOI: 10.1016/j.jimonfin.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Current accounts and oil price fluctuations in oil-exporting countries: The role of financial development

Abstract: Oil-exporting countries usually experience large current account improvements following a sharp increase in oil prices. In this paper, we investigate this oil price-current account relationship on a sample of 27 oil-exporting economies. Relying upon the estimation of panel smooth transition regression models over the 1980-2010 period, we provide evidence that refines the traditional interpretation of oil price effects on current accounts. While current accounts are positively affected by oil price variations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 46 publications
9
38
0
Order By: Relevance
“…Moreover, the literature shows that the relative growth and demographic variables are negatively related to the current account (Chinn & Prasad, ; Christiansen, Prati, Ricci, & Tressel, ; Phillips et al, , among others). The negative relationship between financial deepening and the current account is also in line with several empirical studies (Gruber & Kamin, ; Cheung, Furceri & Rusticelli, ; Allegret, Couharde, Coulibaly, & Mignon, ), including those on the Sub‐Saharan African (SSA) countries (Gnimassoun, ). More trade openness is also often associated with a current account deficit (see Chinn & Prasad, ; Arezki & Hasanov, ; Allegret et al, , among others).…”
Section: The Empirical Relationship Between the Current Account And Tsupporting
confidence: 85%
“…Moreover, the literature shows that the relative growth and demographic variables are negatively related to the current account (Chinn & Prasad, ; Christiansen, Prati, Ricci, & Tressel, ; Phillips et al, , among others). The negative relationship between financial deepening and the current account is also in line with several empirical studies (Gruber & Kamin, ; Cheung, Furceri & Rusticelli, ; Allegret, Couharde, Coulibaly, & Mignon, ), including those on the Sub‐Saharan African (SSA) countries (Gnimassoun, ). More trade openness is also often associated with a current account deficit (see Chinn & Prasad, ; Arezki & Hasanov, ; Allegret et al, , among others).…”
Section: The Empirical Relationship Between the Current Account And Tsupporting
confidence: 85%
“…The deterioration of current account balances could be attenuated by well-developed financial systems (Allegret et al 2014). Over the medium-to long term, FDI flows to the energy and extractive sector, which contributed significantly to dynamic capital inflows to Sub-Saharan Africa and other developing regions in recent years, may decline if new oil and gas projects become unviable at current oil price levels.…”
mentioning
confidence: 99%
“…For instance, Allegret et al . () focused on current account position. Awartani and Maghyereh (), Jouini and Harrathi () and Salisu and Isah () analyses were centred on stock price– oil price shock.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of these studies found a significant and robust effect of oil price shock on some macroeconomic variables. For instance, Allegret et al (2014) focused on current account position. Awartani and Maghyereh (2013), Jouini and Harrathi (2014) and Salisu and Isah (2016) analyses were centred on stock price-oil price shock.…”
Section: Literature Reviewmentioning
confidence: 99%